Chemical gas-generating nanoparticles for tumor-targeted ultrasound imaging and ultrasound-triggered drug delivery. (November 2016) - Min, Hyun Su; Son, Sejin; You, Dong Gil; Lee, Tae Woong; Lee, Jangwook; Lee, Sangmin; Yhee, Ji Young; Lee, Jaeyoung; Han, Moon Hee; Park, Jae Hyung; Kim, Sun Hwa; Choi, Kuiwon; et al.
Abstract: Although there is great versatility of ultrasound (US) technologies in the real clinical field, one main technical challenge is the compromising of high quality of echo properties and size engineering of ultrasound contrast agents (UCAs); a high echo property is offset by reducing particle size. Herein, a new strategy for overcoming the dilemma by devising chemical gas (CO2 ) generating carbonate copolymer nanoparticles (Gas-NPs), which are clearly distinguished from the conventional gas-encapsulated micro-sized UCAs. More importantly, Gas-NPs could be readily engineered to strengthen the desirable in vivo physicochemical properties for nano-sized drug carriers with higher tumor targeting ability, as well as the high quality of echo properties for tumor-targeted US imaging. In tumor-bearing mice, anticancer drug-loaded Gas-NPs showed the desirable theranostic functions for US-triggered drug delivery, even after i.v. injection. In this regard, and as demonstrated in the aforementioned study, our technology could serve a highly effective platform in building theranostic UCAs with great sophistication and therapeutic applicability in tumor-targeted US imaging and US-triggered drug delivery.